The Anti-Inflammatory Activity of Humic Acid from Borneo Peat Soil in Mice - Rusliandi Rusliandi; Diah Wulandari Rousdy; Mukarlina Mukarlina (Majalah Obat Tradisional, 2020)
Humic acid is a humus compound found in peat soil. Humic acid can potentially be used as an anti-inflammatory compound. This study aimed to determine the effect of humic acid on the volume of foot mice edema and to find the best dose that can suppress the degree of edema volume. The animal object was Swiss mice weighing 25-30 grams and 3 months old. The study used Randomized Block Design (RBD) with positive control, negative control and humic acid treatment with dose 62.5 mg kg-1BW, 125 mg kg-1BW, and 250 mg kg-1BW. The result of this research showed that edema inhibition by the administration of humic acid dose 62,5; 125; 250 mg kg-1 had inflammatory inhibition percentage 2.67%, 13.34%, and 20.01% respectively in 5-hour observation. The best dose of humic acid to suppress inflammation in the mice's paw is a humic acid dose of 250 mg kg-1 compared with value 23.3% of sodium diclofenac as the positive control.